PENGARUH LEVEL SUPLEMEN TERNAK ORGANIK YANG BERBEDA PADA FERMENTASI BATANG PISANG TERHADAP KARAKTERISTIK FISIKOKIMIA - Lou, Stefania; Marhaeniyanto, Eko; Thiasari, Nurita (Fakultas Pertanian, 2017)
This study aimed to determine the effect of different levels of organic livestock supplements (STO) on banana stem fermentation to physicochemical characteristics including pH, color, shape, texture and odor, dry matter, crude fat. The main ingredients in this study were banana sticks and STO with rice bran as extra material. This study used a Completely Randomized Design (CRD) experiment with 5 treatments and 5 replications and 21 days of ripening. P0: 100% banana stem + 10% without addition of STO, P1: 100% banana stem + 10% rice bran + 0.1% STO, P2: 100% banana stem + rice bran 10% + 0, 2% STO, P3: Banana stem 100% + rice bran 10% + 0.3% STO, P4: 100% banana stem + rice bran 10% + 0, 4% STO. Based on the results of organoleptic test of banana stem fermentation using STO there were no changes in color, texture, odor or shape. Excellent pH treatment was found in P1 with pH 4.0, P0 and P2 with pH 4.1 P3 and P4 pH 4.3 but there was no significant effect between treatments (P>0.05). The nutrient content of dry and crude fat in banana stem fermentation showed very different treatment (P0,05). Kandungan nutrisi bahan kering dan lemak kasar pada fermentasi batang pisang menunjukkan antara perlakuan berbeda sangat nyata (P